The disordered body : epidemic disease and cultural transformation - Hatty, Suzanne (SUNY series in medical anthropology., 1999)
"The Disordered Body presents a fascinating look at how three epidemics of the medieval and Early Renaissance period in Western Europe shaped and altered conceptions of the human body in ways that continue today. Authors Suzanne E. Hatty and James Hatty show the ways in which concepts of the disordered body relate to constructions of disease. In so doing, they establish a historical link between the discourses of the disordered body and the constructs of gender. The ideas of embodiment, contagion and social space are placed in historical context, and the authors argue that our current anxieties about bodies and places have important historical precedents. They show how the cultural practices of embodied social interaction have been shaped by disease, especially epidemics."--Jacket.